An approach for teleseismic location by automatically matching depth phase - Yuan, Jianlong; Ma, Huilian; Yu, Jiashun; Liu, Zixuan; Zhang, Shaojie (Frontiers in Earth Science, 2025)
To deal with the low efficiency problem of accurate teleseismic hypocenter location, this paper proposes a fully automatic approach by integrating the advantages of Seismic-Scanning based on Navigated Automatic Phase-picking, which can automatically detect and locate seismic events from continuous waveforms, and the Depth-Scanning Algorithm, which can determine the precise focal depth of local and regional earthquakes by matching depth phases. This approach, named TeleHypo, automatically searches and downloads seismic station data from the Data Management Center of the Incorporated Research Institutions for Seismology according to the original time and centroid location of teleseismic earthquakes reported by the Global Centroid-Moment-Tensor Project. Then, the direct wave was automatic extracted to construct depth-phase templates. All possible depth phases after the direct phase are obtained through a match-filtering method. Finally, high-precision hypocenter depth is determined according to the relationship between the travel time differences of the direct waves and depth phases. TeleHypo can obtain high-precision teleseismic hypocenter parameters automatically through the above process. This approach has been successfully applied to 55 teleseismic events occurred in different global seismogenic regions. It can be used to establish high-quality teleseismic catalogue and depth-phase database.